Identifikasi Bencana dan Evaluasi Pencapaian Tujuan Pembangunan Millenium di Nusa Tenggara Timur - M. Baiquni; Dyah R. Hizbaron (Forum Geografi, 2011)
Regional development in the eastern part of Indonesia has not yet sufficient to achieve the aspect of Millennium Development Goals. At the aftermath of sustainable development ratification, three major concepts of social, economic and environmental pillars should be equally translated into the planning agenda. Unfortunately, the methods to analyze the environmental condition have not yet developed in the Indonesian planning culture. This article aimed at the development of the environmental method analysis using the identification of hazard and evaluation of the millennium development goals in the case study area of East Nusa Tenggara. The development of the methods destined to empower the local potential sector. The methods applied the desk study, simple statistical methods and simple matrices to construct the list of priority of problems, and development programs. The result of the research revealed that in East Nusa Tenggara had been experiencing a very low social welfare distribution. Flooding and clean water services were at the same time need to be managed properly to support human development in the frontier region. By strengthening identification towards hazard, and achievement monitoring of MDGs, it is expected that the area soon experience better environmental, social and economic development strategy.